(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Subconductor methods or partial wire methods yield reliable results for conductor parameters such as inductance, capacitance, conductance and resistance and can be used to estimate these parameters for conductor configurations involving complex geometries which cannot be handled using analytical methods. The values of inductances obtained using partial wire method are critically compared with values obtained using analytical methods.